Implementation Of Character Education Through Positive School Culture In Elementary Schools - Kharisma Nurul Azizah; Putri Hasanah Kusumaningrum; Rizka Preti Febriana; Rawanoko, Endrise Septina (Academic Solution Publisher, 2024)
This study aims to determine the implementation of character education through positive school culture in elementary schools. In schools, students do not only gain knowledge but are also equipped with values, rules, manners, and cultural customs. School culture is the atmosphere of life in the school environment where all school residents, including students, educators, counselors, and staff interact and work together. Good character education aims to change individuals to be better. Without a good school culture, it will be difficult to realize positive character education for students. By using the systematic literature review (SLR) method, a literature review method that identifies, examines, evaluates, and interprets all available research. Furthermore, an article review was carried out by reading the entire contents of the article which aims to see the suitability with the research topic and obtained 4 articles that are relevant to the research topic.